Pengaruh Kebijakan Digitalisasi Pendidikan terhadap Motivasi Belajar Siswa Sekolah Menengah - Nursyamsiah (Jurnal Zeniusi, 2025)
This study aims to self-determination theory approach. This theory emphasises the importance of three basic aspects in building intrinsic motivation, namely autonomy, competence, and connectedness. In the context of digital policy, these three aspects are crucial to be studied further in order to understand how technology contributes to students' enthusiasm for learning. The method used is library research with a qualitative approach. Data were collected from various literature sources, such as scientific journals, books, and policy reports that are relevant to the theme of educational digitalisation and learning motivation. The analysis was carried out thematically to explore the relationship between digital policies and students' psychological conditions in the learning process. The results of the study show that digitalisation policies can increase students' learning motivation if supported by adequate facilities, teacher training, and a fun learning approach. However, in areas that are less ready in terms of infrastructure, this policy actually creates gaps and reduces learning enthusiasm. Therefore, an inclusive and contextual implementation strategy is needed so that digitalisation really has a positive impact on students' learning motivation.